The use of constructed wetlands for removal of pesticides from agricultural runoff and drainage: a review - Vymazal, Jan; Březinová, Tereza (Environment international, 2015)
Pesticides are used in modern agriculture to increase crop yields, but they may pose a serious threat to aquatic ecosystems. Pesticides may enter water bodies through diffuse and point sources, but diffuse sources are probably the most important. Among diffuse pollution, surface runoff and erosion, leaching and drainage represent the major pathways. The most commonly used mitigation techniques to prevent pesticide input into water bodies include edge-of-field and riparian buffer strips, vegetated ditches and constructed wetlands. The first attempts to use wetland macrophytes for pesticide removal were carried out as early as the 1970s, but only in the last decade have constructed wetlands for pesticide mitigation become widespread. The paper summarizes 47 studies in which removal of 87 pesticides was monitored. The survey revealed that constructed wetlands with free water surface are the most commonly used type. Also, it has been identified that removal of pesticides is highly variable. The results of the survey revealed that the highest pesticide removal was achieved for pesticides of the organochlorine, strobilurin/strobin, organosphosphate and pyrethroid groups while the lowest removals were observed for pesticides of the triazinone, aryloxyalkanoic acid and urea groups. The removal of pesticides generally increases with increasing value of KOC but the relationship is not strong.
Keywords: Pesticides; Wetlands; mokřady; chemické látky znečišťující vodu; pesticidy; Water Pollutants, Chemical; zemědělství; Agriculture